OSTEO-ARTICULAR DISORDER IN CHILDREN WITH CYSTIC FIBROSIS - Dana-Teodora; Ana-Simona Drochioi; Oana Teslariu; Alina Mariela Murgu; Ioana Cernescu; Alexandra-Dana Ifrim; "G.T. Popa" University of Medicine and Pharmacy, Iasi (Amaltea Medical Publishing House, 2016)
Osteo-articular disorder in cystic fibrosis is considered a common complication of this pathology. The most efficient strategies used for bone health maintenance in patients with cystic fibrosis are early recognition, prevention and correct treatment. The purpose of this study was the clinical and paraclinical evaluation of patients hospitalized in the 3rd Clinic of Pediatrics, "Sf. Maria" Children's Emergency Hospital Iasi, diagnosed with cystic fibrosis that exhibited also symptoms of osteo-articular manifestation. The results from this study support the idea that the association of treatment, calcium, multimineral supplements with appropriate hygienic-dietary regimen and with the background therapy of the disease can contribute significantly to better healthand wellbeing. Also, non-compliance to treatment among patients and their families significantly contributes to early installation of the complications, including the osteo-articular ones (even from the age of 6 years).